Risk Factors for Stunting in Children Aged 24–59 Months in Jambi City, Indonesia, 2024 - Riya, Rosa; Naswir, Mohammad; Johari, Asni; Elrifda, Solha; Huda, Nizlel (Indonesian Journal of Obstetrics and Gynecology, 2026)
Abstract Objective: To analyze factors associated with stunting among children aged 24–59 months at the Tanjung Pinang Community Health Center, Jambi City, Indonesia, in 2024. Methods: This quantitative cross-sectional study involved all stunted children registered at the Tanjung Pinang Community Health Center (n = 42). Total sampling was applied. The independent variables included child age, maternal age, maternal education, economic status, maternal knowledge, and maternal attitude. Data were collected using structured questionnaires with established validity and reliability. Statistical analysis was performed using the chi-square test, with a significance level set at p < 0.05. Results: The analysis showed no significant associations between stunting and child age (p = 0.509), economic status (p = 0.746), maternal education (p = 0.170), maternal knowledge (p = 0.355), or maternal attitude (p = 0.395). However, maternal age was significantly associated with the incidence of stunting (p = 0.024), with a higher risk observed among mothers aged <20 years and >35 years. Conclusion: Maternal age was the only factor significantly associated with stunting among children aged 24–59 months in this study. These findings highlight the importance of targeted interventions focusing on maternal age as part of stunting prevention strategies. Keywords: attitude, economic status, knowledge, maternal age, maternal education, stunting